SARAJEVO - Stefansson, Anders H. (Tidsskriftet Antropologi, 2003)
Anthropological urban studies tend to explore how the specific social structures of cities affect the life of their inhabitants. In contrast, this article analyses local actors’ own cultural constructions of the city and urbanity. It is based on ethnographic fieldwork in Sarajevo, the capital of Bosnia and Herzegovina, a city that suffered heavy destruction during the war in the 1990s. According to native Sarajevans, however, the greatest threat to the unique urban culture of Sarajevo emanated from the radical transformation of the demographic structure that took place during the war, as many people fled Sarajevo while large groups of displaced people from other parts of the country sought refuge in the city. It was a popular perception among the local population that what used to be a modern and cosmopolitan European city in the course of war had deteriorated into “one big village”, plagued by cultural primitivism, ethnic nationalism and intolerance imported by newcomers from the rural backwaters of the country. The article shows how the roots of the powerful cultural dichotomies between city and countryside as well as between cultured and uncultured are to be located in the region’s historical position at the margins of Europe. The article argues that Sarajevans employed displaced persons as politically convenient scapegoats for experiences of social transformation and decay that stemmed more from war and crisis than from the inferior cultural habits of the newcomers.